PENYISIHAN LOGAM CR (VI) DARI LIMBAH CAIR ELEKTROPLATING MENGGUNAKAN ADSORBEN BEADS KOMPOSIT CHITOSAN-CLAY - Putri Fatihah Zuhrah; Shinta Elystia; Zultiniar Zultiniar; Dini Aulia Sari Ermal (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2022)
Water pollution by heavy metals is a serious problem. One of the dangerous parameters that contaminate waters is heavy metals that come from metal industrial waste. Electroplating wastewater contains heavy metals that are harmful and toxic to the environment. Alternative treatment that can be used is the adsorption process with a column system using chitosan-clay beads. Chitosan has amine and hydroxyl groups which have ability to absorb heavy metals. The results of the characterization by FTIR (Fourier Transform Infrared) test on chitosan produced contained a chitosan functional group and obtained a DD value of 80.97%. This study aims to remove Cr (VI) in electroplating wastewater. The variations carried out were variations in the ratio of the composition of chitosan-clay beads (w/w) (1.5:1), (2:1), (2.5:1) and a flow rate 3 mL/minute; 3.5 mL/min; and 4.5 mL/min. The results of the water absorption test (DSA) obtained for each variation of chitosan-clay beads were 609.52%; 628.27%; 658.04%, and the results of the compressive strength test are 22.491; 10,653; 3,015 Kgf. The results obtained are the best Cr (VI) removal efficiency of 95.46% with concentration of Cr (VI) 1.1566 mg/L at the ratio of chitosan-clay beads composition (2,5:1) (w/w) and flow rate 3 mL/min.